2002
DOI: 10.1002/mrd.10040
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the cell membrane fluidity, actin fibers, and mitochondrial dysfunctions of frozen‐thawed two‐cell mouse embryos

Abstract: Physical and chemical alterations caused by the freezing and thawing and their effects on survivals/developments in vitro were investigated. Of a total of 452 two-cell mouse embryos, the overall survival rate of the frozen-thawed embryos was 76.1% (344/452). The blastocyst formation of the frozen-thawed embryos was 32.6% (44/136) compared to 74.5% (117/157) in the fresh embryos (P<0.05). The total number of cells in a blastocyst also decreased from 96.0 +/- 19.0 (n=26) in the fresh embryos to 42.0 +/- 11 .34 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 42 publications
3
66
0
3
Order By: Relevance
“…This would imply that cytotrophoblast and syncytiotrophoblast cells resulting from vitrified embryos might proliferate at a lower rate in contrast to those from slow-freezing embryos. Results from previous studies on mouse embryo showed that vitrification reduced mitochondrial dynamics and increased reactive oxygen species (ROS) production in embryos [25][26][27]. Oxidative stress may trigger the apoptosis cascade in the developmental rate of embryos after thawing [26], which may be an important mechanism underlying the decreased capacity of the vitrified embryo to hCG secretion.…”
Section: Discussionmentioning
confidence: 99%
“…This would imply that cytotrophoblast and syncytiotrophoblast cells resulting from vitrified embryos might proliferate at a lower rate in contrast to those from slow-freezing embryos. Results from previous studies on mouse embryo showed that vitrification reduced mitochondrial dynamics and increased reactive oxygen species (ROS) production in embryos [25][26][27]. Oxidative stress may trigger the apoptosis cascade in the developmental rate of embryos after thawing [26], which may be an important mechanism underlying the decreased capacity of the vitrified embryo to hCG secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In MII mouse and human oocytes and embryos (Ahn et al 2002, 2003, Jones et al 2004, the highest intensity of J-aggregate fluorescence is reported to occur in the pericortical/subplasmalemmal cytoplasm (arrows, Fig. 1K).…”
Section: Is Mitochondrial Polarity (Dc M ) Related To Competence?mentioning
confidence: 97%
“…The apoptotic nuclei were brown after TUNEL staining (arrow events would be triggered from mitochondria, including release of caspase activators (such as cytochrome c), changes in the electron transport, loss of the mitochondrial transmembrane potential, altered cellular oxidation-reduction, and activation of proapoptotic and antiapoptotic Bcl-2 family proteins. Accompanying the underlying biochemical events are many apparent morphologic changes, including cell membrane shrinkage and subsequent loss of membrane integrity (42,43), the translocation of membrane phosphatidylserine (44), and DNA fragmentation (45). Thus, the translocation of membrane phosphatidylserine, the mitochondrial membrane depolarization, and DNA fragmentation detected by the annexin V binding assay, JC-1 staining, and the TUNEL assay, respectively, are good indicators of cellular apoptosis.…”
Section: F I G U R Ementioning
confidence: 99%